Electrochemical Voltammogram Recording for Identifying Varieties of Ornamental Plants - Rutong Yang; Boyuan Fan; Shu’an Wang; Linfang Li; Ya Li; Sumei Li; Yuhong Zheng; Li Fu; Cheng-Te Lin (Micromachines, 2020)
An electrochemical voltammogram recording method for plant variety identification is proposed. Electrochemical voltammograms of Vistula, Andromeda, Danuta, Armandii ‘Apple Blossom,’ Proteus, Hagley Hybrid, Violet Elizabeth, Kiri Te Kanawa, Regina, and Veronica’s Choice were recorded using leaf extracts with two solvents under buffer solutions. The voltametric data recorded under different conditions were derived as scatter plots, 2D density patterns, and hot maps for variety identification. In addition, the voltametric data were further used for genetic relationship studies. The dendrogram deduced from the voltammograms was used as evidence for relationship study. The dendrogram deduced from voltametric data suggested the Andromeda, Danuta, Proteus, Regina, and Hagley Hybrid were closely related, while Violet Elizabeth and Veronica’s Choice were closely related. In addition, Vistula and Armandii ‘Apple Blossom’ could be considered outliers among the varieties.